2017
DOI: 10.3126/jnps.v36i3.15539
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Probiotic Saccharomyces boulardii as an Adjuvant Therapy in Acute Childhood Diarrhoea

Abstract: Introduction: Administration of S. boulardii in addition to rehydration therapy in diarrhea found to be beneficial in many aspects owing to a variety of causes and importantly it is was not associated with any adverse effects.Material and Methods: We conducted a prospective study of children suffering from acute diarrhoea, at a private tertiary care hospital. Children were divided into 2 groups randomly as per odd(Group 1 ) and even (Group 2) bed allotted in indoor at the time of admission: Group 1 included ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 15 publications
1
5
0
Order By: Relevance
“…This was similar to the findings in the RCT study conducted by Das et al., wherein the median duration (hours) of diarrhoea was significantly less in the S. boulardii group (60 versus 89; 95% CI –41.2 to 16.8) compared with the control group [ 10 ]. The same is observed in the RCT carried out by Dash et al., in which the duration of diarrhoea was comparatively less (26.31 versus 47.81 hours) in the group given S. boulardii than the control group [ 13 ]. Another study, by Riaz et al., purported that the duration of diarrhoea was significantly less in the group given S. boulardii by 11.9 (52.1 versus 64.0) hours when compared with the control group [ 14 ].…”
Section: Discussionsupporting
confidence: 74%
“…This was similar to the findings in the RCT study conducted by Das et al., wherein the median duration (hours) of diarrhoea was significantly less in the S. boulardii group (60 versus 89; 95% CI –41.2 to 16.8) compared with the control group [ 10 ]. The same is observed in the RCT carried out by Dash et al., in which the duration of diarrhoea was comparatively less (26.31 versus 47.81 hours) in the group given S. boulardii than the control group [ 13 ]. Another study, by Riaz et al., purported that the duration of diarrhoea was significantly less in the group given S. boulardii by 11.9 (52.1 versus 64.0) hours when compared with the control group [ 14 ].…”
Section: Discussionsupporting
confidence: 74%
“…Studies included in the systematic review (n = 22 RCTs, N = 4059 participants) included 5 single‐strain probiotics and 3 multi‐strained mixtures (Table 1) (43–64). Five types of probiotics were excluded from the meta‐analysis (60–64), as they lacked at least 1 confirmatory trial, resulting in 17 RCTs for the meta‐analysis (20 treatment arms) for 3 probiotics: Saccharomyces boulardii CNCM I‐745 (9 RCTs), Lactobacillus rhamnosus GG (ATCC 53103) (6 RCT, 7 arms), and a 4‐strain mixture of Bacillus clausii O/C, SIN, N/R, T (4 RCTs).…”
Section: Resultsmentioning
confidence: 99%
“…The rapidity of a response was different by the type of probiotic, but not all trials provided data for this outcome (see Table, Supplemental Digital Content 7, Rapidity of Response, http://links.lww.com/PG9/ A46). In 3 RCTs with S. boulardii CNCM I-745 (43,46,48), the number of stools/day were equivalent at day 1 and day 3, but by day 4, the mean number of stools was significantly fewer for S. boulardii compared with controls (SMD, -0.61 stools/day; 95% CI, -1.06 to -0.17…”
Section: Rapidity Of Response (Stool Frequency/day Over Time)mentioning
confidence: 99%
“…Ultimately, 29 RCTs that randomised 4217 participants (2152 in the experimental group and 2065 in the control group) were included . .…”
Section: Resultsmentioning
confidence: 99%
“…Data regarding therapy‐related adverse events were collected in nine studies . In eight of these trials, adverse events were not observed, and in one trial, a single patient in the S boulardii group reported a meteorism .…”
Section: Resultsmentioning
confidence: 99%